Low complexity multidimensional CDF 5/3 DWT architecture - Al-Azawi S.; Abbas Y.A.; Jidin R. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper introduces an efficient low complexity multidimensional DWT architecture. The proposed architecture is based on a lifting-scheme for the Cohen-Daubechies-Feauveau (CDF) 5/3 DWT filter. It consists of low complexity identical computation and control units which can be used easily to implement 2-D and 3-D DWT architectures. The synthesis results show that the output latency is 2N+2 clock cycles, with N2+2N+2 clock cycles required for the first level 2-D CDF 5/3 DWT computation. The architecture is parameterized to tackle various images and wordlength sizes. Furthermore, the proposed architecture is implemented using a Virtex 6 Xilinx FPGA platform. The implementation results reveal that the proposed architecture can operate at up to 198 MHz operating frequency. This reduces the time for first level DWT decomposition of a 512×512-pixel image to less than 1.3 m sec. © 2014 IEEE.